Automatic abstraction for model checking software systems with interrelated numeric constraints. - Choi, Yunja (Software engineering notes.)
Model checking techniques have not been effective in important classes of software systems characterized by large (or infinite) input domains with interrelated linear and non-linear constraints over the input variables. Various model abstraction techniques have been proposed to address this problem. In this paper, we wish to propose domain abstraction based on data equivalence and trajectory reduction as an alternative and complement to other abstraction techniques. Our technique applies the abstraction to the input domain (environment) instead of the model and is applicable to constraint-free and deterministic constrained data transition system. Our technique is automatable with some minor restrictions.